Inovasi Layanan Sistem Informasi Kesehatan Terpadu Berbasis Website Di Dinas Kesehatan Kabupaten Bantaeng - Nursanti, Nursanti; Madani, Muhlis; Abdi, Abdi (Universitas Muhammadiyah Makassar, 2022)
This study aimed to identify to improve public services in the field of reporting data and informationtothe Bantaeng Regncy health office. Using manual systems towards innovation based integrated health information systems website. This study used qualitative. Data collection techniques used interviews, observation, and documentation. The informants who involved in website-based system innovation. The data were analyzed qualitatively. Thi study showed that an integrated health information system based innovation website had advantages, suitability, complexity, possibilities to try and simplicity too bserve. Thiswebsite-based integrated health information system was an innovation that had several factors, namely desire to change for the better the availability of facilitiesand Service Improvement Pressure. However, there were also some inhibiting factors, such as Administrative Pressure and Barriers and Risk Aversion Culture. Keywords: website-based service innovation